Catalytic effect of silver in reducing metronidazole in human blood and water samples. (May 2022) - Ettadili, F.E.; Matrouf, M.; Alaoui, O. Tahiri; Laghrib, F.; Saqrane, S.; Farahi, A.; Bakasse, M.; Lahrich, S.; El Mhammedi, M.A.
Abstract: In the present paper, the metallic silver electrode (MSE) was employed for the electrochemical reduction of metronidazole (MTZ). The MTZ had a well-defined reduction peak at −554 mV in 0.1 mol L −1 sodium sulfate solution (Na2 SO4, pH = 5.6). The MSE lowered its reduction potential when compared with the glassy carbon electrode (GCE). Under optimum conditions, the reduction peak current was proportional to the concentration of MTZ in the range of 8.0×10 −6 to 2.0×10 −3 mol L −1 . The detection limit (DL) was found to be 1.43×10 −6 mol L −1 . The proposed method was also applied for the determination of MTZ at MSE in river, waste, tap water, and human blood samples.